Formulation Strategies and Recent Advances in Floating Drug Delivery System (FDDS): A Comprehensive Review - Sankhe Lochani D,; Khaire Rahul D,; Kathale Ankita A,; Bhandare Tejaswini S,; Ghude Samiksha K, (Asian Journal of Pharmaceutical Research and Development, 2025)
Floating Drug Delivery Systems (FDDS) represent a state-of-the-art oral drug delivery strategy, designed particularly to enhance gastric retention of dosage forms. The floating systems float for long durations in the stomach, allowing for extended drug release and increasing the bioavailability of drugs absorbed predominantly in the upper gastrointestinal tract. FDDS are collectively categorized into effervescent and non-effervescent systems, both having different mechanisms of floating. Different formulation methods—ionotropic gelation, spray drying, melt granulation, hot-melt extrusion, solvent evaporation—have been used to produce various floating systems such as tablets, capsules, beads, and microspheres. This review presents a comprehensive analysis of FDDS, such as types, polymers employed, formulation approaches, evaluation techniques, and conditions affecting gastric retention. It also points towards recent developments, including 3D printed systems, nano-FDDS, and magnetically controlled drug delivery platforms, providing indications of the future potential of floating systems in controlled and targeted drug release.